Total colorectal duplication in an infant presenting with fecaluria as the initial symptom - Ab. Rahman, Norhafiza; Malek, Nik Fatimah Salwati; Nallusamy, Mohan Arunasalam (2019)
An 11-month old boy presented with 2 months history of progressive abdominal distension. The current presentation was preceded by an initial presentation of fecaluria during the neonatal period. Digital rectal examination revealed a firm mass anterior to the rectum. Computed tomography (CT) of the abdomen and pelvis showed a long tubular structure adjacent to the native colon and rectum filled with fecal material. He underwent fenestration of the tubular colorectal duplication and recovered well. We report a case of duplicated colon and rectum with a unique initial presentation of fecaluria during the neonatal period.